Vamos refletir sobre a prática? Apresentação de uma ferramenta reflexiva para sustentar o raciocínio profissional em terapia ocupacional - Gomes, Laysla Demonari (Universidade Federal de São Carlos, 2021)
Professional practices have been investigated from the perspective of the Epistemology of Practical Rationality, which understands that the practice as a complex, singular, uncertain and permeated by a conflict of values phenomena, and for which is possible and necessary to build practical knowledge. One of the ways to understand professional practice in occupational therapy embraces research on reflexive processes and clinical/professional reasoning. Professional reasoning has been investigated since the 1980's, with a growing number of works since then. This research is the result of a previous research that aimed at building a reflexive tool to support professional reasoning in occupational therapy in the process of identifying needs in the practice scenario of Primary Health Care (PHC). To better understand the potential of this tool for reflection on practice, it was necessary to analyze its content and its practical applicability by occupational therapists of other PHC services. Eleven occupational therapists from the state of São Paulo, identified by snowball sampling, participated utilizing the tool, analyzing it through an online questionnaire of agreement, and suggesting modifications through comments in the questionnaire, in individual interviews and in a group interview - conducted after a first change of the tool. The data analysis was carried out in a descriptive way for the agreement data from the questionnaire and thematic analysis for the interviews. The results demonstrate the applicability of the tool in the practice of occupational therapists, emphasizing the promotion of reflection on practice; the greater clarity in identifying the core of occupational therapy interventions presenting them to PHC teams; and its applicability to other contexts of professional practice.
Let's think about the practice? Presentation of a reflexive tool to support professional reasoning in occupational therapy
Keywords: Terapia ocupacional; Prática profissional; Raciocínio clínico; Ferramenta reflexiva; Occupational therapy; Professional practice; Clinical reasoning; Reflective tool; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL